COMPARATIVE CHARACTERISTICS OF MFR PLASTIC OPERATIONS - Khalikov Azizbek Alimurodovich, Rakhmatov Jakhongir Bakhodirovich, Musaev is the son of Sirojiddin Chori, Mengkobilov Umar Khushbokovich (American Journals Publishing, 2022)
When performing complex and lengthy microsurgical operations, the surgeon must have optimal facilities for working under a microscope, which would protect him from fatigue and maintain efficiency.